Evaluation of Hepatitis C in 20 Years: A Turkish Experience - Nagehan Didem Sarı; Sevim Baltalı; İstemi Serin (Bagcilar Medical Bulletin, 2023)

(untitled)
Objective: Hepatitis C virus (HCV) infection still maintains its importance since it is one of the most important causes of liver cirrhosis and hepatocellular carcinoma. Our hospital, located in İstanbul, which is the 10t most crowded city in the world, has a patient cohort where epidemiological change can be observed due to its deep-rooted history and serving people of different nations in terms of settlement. Main aim in this study is to evaluate the change in HCV epidemiology in our country over the years. Methods: Patients who were at the age of 18 and above and whose HCV-RNA was positive between January 2001 and January 2021 were evaluated. Results: 1.166 patients whose HCV genotype was determined were evaluated. The mean age of the population is 52±14.75 years, 83.53% of all patients was infected with genotype 1 (GT1), 8.23% with GT3, 5.83% with GT2, 2.23% with GT4 and 0.17% of them with GT5. While the GT1 rate decreased in patients over the years, an increase was found in other GTs. GT1 and GT2 were more common in females (p<0.001); GT3 and GT4 were more dominant in males (p<0.001). The mean age of females was high in all genotypes. The mean age of GT3 was significantly lower than the other groups (p<0.001). Conclusion: Although GT1 is still dominant in our country, GT3 and GT4 have been increasingly seen over the years, suggesting that the genotype distribution may change in the coming years due to uncontrolled migration and effective direct-acting antivirals.